Diversity and spatial distribution of Lauraceae tree species in Lower Montane Forest at Doi Suthep-Pui National Park, Northern Thailand - SIRIPHUM SRISUWAN; SARAWOOD SUNGKAEW; CHONGRAK WACHRINRAT; LAMTHAI ASANOK; TORLARP KAMYO; SATHID THINKAMPHEANG; PANIDA KACHINA; SUTHEERA HERMHUK; WONGSATORN PHUMPHUANG; ARERUT YARNVUDHI; DOKRAK MAROD (Society for Indonesian Biodiversity, 2024)
Abstract. Srisuwan S, Sungkaew S, Wachrinrat C, Asanok L, Kamyo T, Thinkampheang S, Kachina P, Hermhuk S, Phumphuang W, Yarnvudhi A, Marod D. 2024. Diversity and spatial distribution of Lauraceae tree species in Lower Montane Forest at Doi Suthep-Pui National Park, Northern Thailand. Biodiversitas 25: 3510-3520. Montane forests are characterized by high plant diversity, including a notable representation by the Lauraceae family, which offers a variety of ecological and economic benefits. This study aimed to assess the species diversity, spatial distribution, and habitat suitability of the Lauraceae family in the Doi Suthep-Pui National Park, Northern Thailand. A Generalized Linear Model (GLM) was employed to determine the spatial distribution of the dominant Lauraceae species, whereas the Maximum Entropy (MaxEnt) model was used to assess habitat suitability for key species. A total of 24 species across 10 genera were found. The most species-rich genera were Cinnamomum and Litsea, followed by Cryptocarya, Machilus and Phoebe, and Actinodaphne, Persea, Beilschmiedia, and Neocinnamomum. Habitat suitability for important Lauraceae species was categorized into low-, medium-, and high-potential areas. The elevation and soil organic matter were the most significant factors influencing species abundance. Additionally, soil properties also played a role in species distribution. The spatial distribution of Lauraceae species was primarily influenced by elevation. However, this distribution is also influenced by the interplay between elevation, soil properties, climate, and human activity. Thus, a comprehensive knowledge of these determinants can inform conservation strategies and ensure the long-term viability of Lauraceae populations in montane forests.